The role of food systems and value chains to improve diets in low income settings: Diagnostics to support intervention design in Malawi - Gelli, Aulo; Donovan, Jason; Margolies, Amy; Aberman, Noora-Lisa; Santacroce, Marco; Chirwa, Ephraim; Henson, Spencer; Hawkes, Corinna (International Food Policy Research Institute, 2018)
In this paper, we apply a mixed-method multisectoral diagnostic to examine potential interventions in food systems to improve diets of rural smallholder farmers in Malawi. We examine the entry points for interventions involving public and nonprofit (including both government and development partners) and private-sector perspectives. In addition, we explore the methodological and theoretical requirements for undertaking this type of multisectoral analysis.